Effects Of Iron And Zinc Supplementation On Growth And Morbidity Status Of Undernourished Infants (6-12 Months Old) From Rural Villages In Kelantan - Yim, Hip Seng (2001)
Stunting in children is a common form of undernutrition in developing countries. Deficiency of micronutrients including iron and zinc has been associated with growth faltering in young children. The aim of the study was to assess the effects of iron and zinc supplementation on the growth and morbidity status of undernourished infants from rural villages in the district ofKota Bharu, Kelantan. A six months randomised, double-blind, placebo-controlled study was conducted on 9S undernourished (weight-for-age Z score < -1.0 SD of NCHS reference) infants aged 6- 12 months. The infants were divided into 5 groups, comprising 4 supplementation and a placebo groups: Group I-Fe (20 mg/week) + Zn (17 mg/week) with vitamins A (1700 Ug/week) and C (20 mg/week); Group II-Fe with vitamins A and C; Group III-Zn with vitamins A and C; Group IV-Fe + Zn only; and Group V-Placebo (plain syrup). Length, weight and circumferences of mid-upper arm (MUAC), head and chest were measured monthly. Morbidity status as indicated by symptoms including diarrhoea, fever, cough, running nose and vomiting was recorded by interviewing the mothers fortnightly. Information on feeding practices, use of complementary foods and their nutrient intake were also obtained from the mothers.